PREVALENCE RATE OF DYSCALCULIA AMONG PRIMARY SCHOOL STUDENTS - Jyoti,; Rekha, (International Journal of Psychosocial Rehabilitation, 2020)
In the modern world, mastery over basic academic skills- reading, writing and arithmetic is a necessary pre-requisite for success in all walks of life. In fact, numeracy skills are needed for effective citizenship in knowledge based society. These skills provide the base to an individual to realize his/her potentialities. Impairments of skills in these areas among children, which occur despite appropriate levels of intelligence and opportunities to learn, are termed as specific learning disabilities. There are a great number of students who have serious difficulties in learning mathematics, but find the rest of academic subjects easy. These students have high IQs, are excellent readers, creative writers and learn quickly. But when it comes to any subject that requires understanding and application of the language of mathematics, they fail miserably (Newman, 1998). The goal of the investigator was to identify the students of Grade III who seem to have learning disabilities in mathematics. The prevalence rate of dyscalculia among Primary School Students studying in English Medium Schools of Yamuna Nagar district of Haryana was found to be 7.1%